Experimental Study of Quenching Process During Bottom Reflooding Using “Queen” Test Section - M. Juarsa; A.R. Antariksawan; P. Joko; H. Ismu; S. Edy; Kiswanta Kiswanta (Atom Indonesia, 2005)
Phenomenon of quenching of hot fuels in core during bottom reflooding following loca event is investigated in order to understand the performance cooling process. the study is conducted experimentally using queen test section which allow study of rod surface temperature histories based on which the heat fluxes are estimated. the visual observation is also done to study the boiling regimes. the test variables are initial rod temperature, i.e. 400oc, 500oc and 600oc, and coolant flow rate, i.e. 0,01kg/s, 0.02 kg/s and 0.04 kg/s with constant water inlet temperature of 30oc. the results shows different heat transfer regimes such as film boiling, transition boiling, nucleate boiling and convective single phase heat transfer regimes. for specified initial rod temperature, the higher flow rate provides high rewet velocity and higher maximum heat flux, then quenching process is more effective.